2020
DOI: 10.3390/ijerph17186468
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Acceptance of the COVID-19 Impact on Shifting Higher Education to Distance Learning in Poland

Abstract: This paper is dedicated to the higher education institutions shifting towards distance learning processes due to the global pandemic situation caused by COVID-19 in 2020. The paper covers the pandemic situation in Poland generally, analyzing governmental ordinances and tracking the gradual extension of restrictions for educational institutions. The purpose of this study is to investigate the influence of Experience, Enjoyment, Computer Anxiety, and Self-Efficacy on students’ acceptance of shifting education to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
209
1
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(252 citation statements)
references
References 43 publications
30
209
1
12
Order By: Relevance
“…This is why they do not manifest computer anxiety. In the previous study, hypothesis H8 (CA ≥ PEOU) was also not confirmed, while hypothesis H7 (CA ≥ PU) was supported; however, its f 2 effect size was very small (less than 0.02) [16].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This is why they do not manifest computer anxiety. In the previous study, hypothesis H8 (CA ≥ PEOU) was also not confirmed, while hypothesis H7 (CA ≥ PU) was supported; however, its f 2 effect size was very small (less than 0.02) [16].…”
Section: Discussionmentioning
confidence: 69%
“…The data for assessing the structural model and the testing proposed hypotheses were collected with a questionnaire in Google Forms. This questionnaire was already tested in a previous study [16]. This study was adjusted to measure expectations, and one additional variable (Subjective Norms) was added to the list.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Polish researchers have studied these changes. For example, one study found a negative but nonsignificant relationship between Poles’ use of public transport and the number of new cases of COVID-19 [ 8 ], and another study discussed students’ acceptance of higher education’s shift to distance education modes of delivery [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the path coefficient of consumer behavior is generally recognized as the minimum value, the path coefficient of the leisure activity intention was confirmed, based on previous studies, with the leisure rumination that was regarded as a fair value [ 80 , 81 , 82 , 83 ]. To verify the hypotheses of this study, an analysis of the significance of the path coefficients was conducted.…”
Section: Resultsmentioning
confidence: 87%